The Influence of Perceived Organization Support (POS) on Negative Staff Turn-Over (Retention) in African Union-United Nations Hybrid Mission Operations in Darfur-Sudan (UNAMID) - Osoo, George M.; Wezel, Prof. Filippo (European Journal of Business and Strategic Management, 2016)
Purpose: The purpose of this study was to establish the influence of Perceived Organization Support (POS) on negative Staff Turn-Over (retention) in African Union-United Nations Hybrid Mission Operations in Darfur-Sudan Methodology: The research design used for this study was a descriptive survey design. This involves explanation of causes and effects of the independent and dependent variables associated with the problem. The study population was 1,242 international staff, 520 UN volunteers and 3,019 national personnel and this was a total of 4781 personnel. The sample size was 200 respondents. Data was collected by the use of questionnaires. The questionnaire consists of both closed and few open ended statements. Data was analyzed mainly by use of descriptive and inferential statistics. Descriptive statistics included mean. Inferential statistical techniques like correlation and regression coefficients were used. Results: The findings indicated that perceived organization support (POS) was a strong determinant of negative Staff Turn-Over (retention) since it was statistically significant in explaining turnover. Unique contribution to theory, practice and policy: The management of UNAMID will be able to appreciate the importance of perceived organization support (POS)in the retention of employees. Additionally, human resource managers will be able to establish competitive human resource practices that are meant to control negative Staff Turn-Over (retention). The study recommends that the management of UNAMID in Sudan to conduct a market survey in order to establish optimal remuneration levels for UNAMID employees in order to control and mitigate the outcomes that are associated with negative Staff Turn-Over (retention).